Hydro-Physical Properties of Soil Treated with Rice Straw-Based Hydrogels - El-Hady, Omar A.; Basta, Altaf H.; El-Saied, Houssni; Shaaban, Said M. (Journal of Composites and Biodegradable Polymers, 2015)
The Present work deals with evaluating rice straw (RS)-based hydrogels, as conditioners for improving the hydro-physical properties of sandy calcareous soils. In this respect, some hydro-physical properties of the soil were examined at the end of three successive growing seasons. Completely randomized field experiments, with three replications for each treatment, were conducted at El-Saff-Giza Governorate, Egypt (summer season 2010 using tomatoes v. cusstle rock, winter season 2010-2011 using wheat v. Seds 1 intercropped with onion v. Giza 20, and summer season 2011 using caw pea v. Bafb as indicator crops), The results obtained show that, applying the RS-based hydrogels provides: (a) Improving in soil structure, which was expressed by water stable structural units (> 0.25 mm in diameter), structural coefficient, dry stable structural units (> 0.84 mm in diameter) and wind erosion parameters. This improvement indicates the high resistance of the soil against both wind and water erosion, as well as destruction of the soil by tillage operations. Moreover, it leads to decrease soil bulk density and macroporosity (drainage pores) on the expense of micro ones. Therefore, water holding pores (the retained moisture in the soil) were increased. Increasing the retained moisture in the soil was noticed at all suctions under study (from 0-15atm). (B) Decreasing the mean diameter of soil pores and in turn its water transmitting properties, namely hydraulic conductivity and transmissivity for vertical flow of water through soil profile. (C) Doubling the rate of applied hydrogels from 2gkg-1 to 4gkg-1 soil leads to great improvement in hydro-physical properties of soil, whereas applying the later rate of hydrogel provides improvement in moisture retention of the treated soil to become over than the requirements of the growing plants. Also, it has adverse effect on the aeration of the root zone as a result of increasing the soil micro-porosity on the expense of its macro ones. Therefore, 2g hydrogel kg-1 soils is recommended dose to get use the RS-hydrogels as benefit soil conditioner, without adverse effects on growth, water and fertilizers efficiency by plants.